Application analysis of disconnecting circuit breaker in different substation arrangements - Cardoso, Elvanger Santos; Filho, Antônio César G. Motta; Monteiro , Paulo Roberto Duailibe; Gomes, Larisa Alves (Seven Editora, 2023)
This work aims to make a comparison between disconnector circuit breakers (DCB) and conventional circuit breakers, with the purpose of evaluating the feasibility of implantation in several installations in Brazil that follow procedures and regulations of the agents of the Brazilian electric sector. The development of DCB technology has allowed an increase in the reliability and availability of the substations, which has contributed to the reduction of failures and, consequently, of the costs related to the maintenance of the substations that incorporate these types of circuit breakers in their projects [1]. It is worth mentioning that, due to the innovative technology of combining two functions (circuit breaker and disconnector) in the same protection device, DCB are not only reducing the amount of raw materials and the emission of gases that favor global heating, but also a relevant reduction of the space occupied by substations that adopt these types of devices in their projects, about 75%, thus resulting in substations more ecologically and economically sustainable substations [1, 2]. DOI:https://doi.org/10.56238/alookdevelopv1-017